2004
DOI: 10.1002/jbm.a.30094
|View full text |Cite
|
Sign up to set email alerts
|

Bone formation and bioresorption after implantation of injectable β‐tricalcium phosphate granules–hyaluronate complex in rabbit bone defects

Abstract: The objective of this study was to evaluate the effects of a complex of beta-tricalcium phosphate (beta-TCP) granules and 3.5% hyaluronate (beta-TCP granules-HY complex) compared with a beta-TCP block, in terms of osteoconductivity and biodegradability, to determine whether this complex would be a good candidate for bone void filler. Both materials were implanted into cavities drilled in rabbit femoral condyles. New bone formation and mineral apposition rate were evaluated to analyze osteoconductivity, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
133
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(148 citation statements)
references
References 58 publications
13
133
1
1
Order By: Relevance
“…Nonetheless, it is important that bone regeneration should accompany the complete absorption of bone substitute material. Chasono et al 8) reported that although the absorption phase of β-TCP granules was totally completed with favorable bone formation, a little remnant of this material could be observed. Further, Gaasbeek et al 1) reported that clinically accepted remnants of β-TCP grafted for an osteotomy gap after high tibial osteotomy were observed from biopsy samples taken more than six months after graft surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is important that bone regeneration should accompany the complete absorption of bone substitute material. Chasono et al 8) reported that although the absorption phase of β-TCP granules was totally completed with favorable bone formation, a little remnant of this material could be observed. Further, Gaasbeek et al 1) reported that clinically accepted remnants of β-TCP grafted for an osteotomy gap after high tibial osteotomy were observed from biopsy samples taken more than six months after graft surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the objective was to assess the potential of highly pure, porousβ-TCP granules, OSferion ® (Olympus Biomaterial Corp., Tokyo, Japan), as a scaffold for bone regeneration. One contributing reason for using OSferion ® in this study was that it has been reported that OSferion ® was absorbed with favorable bone formation 8) . Rat mandibular bone defects were thus grafted with OSferion ® with or without allogenic bone, and then the bone formation and absorption rates were evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the acknowledged excellent biocompatibility of calcium phosphate ceramicsbased materials [1][2][3]5], the present in vitro study demonstrated some differentiation between chemically similar biomaterials. This may be the reason of the variable clinical performance, but we are not in command of in vivo comparison at the moment.…”
Section: Discussionmentioning
confidence: 66%
“…They should also resorb and be replaced by newly formed bone [1][2][3]. As many studies have demonstrated, although autografts are the most suitable bone augmentation materials, their limited availability in the oral tissues and their high rate of post surgical morbidity has motivated investigators to utilize other biomaterials in bone regeneration [2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…Eight weeks after surgery, most of the b-TCP was absorbed and replaced by newly formed bone in the HGF-treated group, whereas b-TCP granules remained in defected regions without HGF. Previous studies indicated that osteoclasts are of major importance in bioresorption of b-TCP [28]. Inhibition of osteoblast formation resulted in reduced b-TCP resorption and bone formation, suggesting a coupling between osteoclast-mediated b-TCP resorption and bone formation [29].…”
Section: Discussionmentioning
confidence: 99%